A clinical warning in the treatment of chlorfenapyr poisoning - Yuelei Cheng; Yunlai Zhao; Hao Li; Minmin Duan; Lianxiang Li; Song Zhou; Qingbin Tang; Wei Xie; Jixue Shi (Toxicology Reports)
Chlorfenapyr, an arylpyrrole-based insecticide, disrupts mitochondrial oxidative phosphorylation to deprive the target organism of energy. Chlorfenapyr poisoning in humans causes distinct clinical signs such as hyperhidrosis, malignant hyperthermia, rhabdomyolysis, and delayed neurological symptoms that worsen over time and can be fatal. When treating acute chlorfenapyr poisoning, physicians must consider the latent period and not assume that a patient is safe after an initial response to treatment. It is important to take measures before sudden, fatal symptoms appear. This paper presents three cases of chlorfenapyr poisoning as a warning for physicians to understand its clinical course and treatment.